Protocol for fabrication of the absorption-based regenerable microporous membrane for ultrafast and energy-efficient removal of antibiotics - Yu Wang; Taoyang Wang; Mengyue Wang; Xiaoling Wang; Junling Guo (STAR Protocols, 2023)
Summary: Traditional techniques for pollutant removal (e.g., static absorption and membrane nanofiltration) are either time consuming or energy intensive with limited permeances. Here, we demonstrate a protocol to fabricate polyamide (PA)-based regenerable adsorption-based membranes (PArab) for ultrafast removal of antibiotics. This protocol describes how to determine the distribution of nanocoatings through the membrane. We also detail the antibiotics removal performance and the regeneration tests.For complete details on the use and execution of this protocol, please refer to Wang et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.